(untitled) (Jurnal Bahasa, 2003)
The language of Islamic management is the language that links its users with Allah s. w.t., for example, initiate work with full commitment and sincerity using ’bismillah’, thank God for a job well-done using ’alhamdulillah ’, or strongly wish to do something in the future with ’insya-Allah ’. Such a linguistic relationship ties man to his Creator, and differs from other language of management that liberates man from God, and from metaphysical beliefs such as secularism, liberalism, modernism and others.